2018
DOI: 10.1596/29779
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Agricultural Resilience through Better Risk Management in Zambia

Abstract: Some rights reserved This work is a product of the staff of The World Bank with external contributions. The findings, interpretations, and conclusions expressed in this work do not necessarily reflect the views of The World Bank, its Board of Executive Directors, or the governments they represent. The World Bank does not guarantee the accuracy of the data included in this work. The boundaries, colors, denominations, and other information shown on any map in this work do not imply any judgment on the part of Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…Droughts and floods are therefore more likely to affect households in zones I and II. This corroborates our earlier findings in section 5.1 and earlier studies suggesting that droughts are the most common climate shock in Zambia (Braimoh et al, 2018; Table 2). While it is difficult to say whether these changes in rainfall patterns lead to poverty or not, what is clear from the data is that chronic poverty-that is, households that are poor across all the three survey rounds-concentrates in parts of the Southern, Eastern, Muchinga, and North-Western Provinces (Figure 3).…”
Section: Exposure Vulnerability and Resilience Among Rural Smallholders In Zambiasupporting
confidence: 93%
See 4 more Smart Citations
“…Droughts and floods are therefore more likely to affect households in zones I and II. This corroborates our earlier findings in section 5.1 and earlier studies suggesting that droughts are the most common climate shock in Zambia (Braimoh et al, 2018; Table 2). While it is difficult to say whether these changes in rainfall patterns lead to poverty or not, what is clear from the data is that chronic poverty-that is, households that are poor across all the three survey rounds-concentrates in parts of the Southern, Eastern, Muchinga, and North-Western Provinces (Figure 3).…”
Section: Exposure Vulnerability and Resilience Among Rural Smallholders In Zambiasupporting
confidence: 93%
“…Alfani et al (2019) found that the 2015/2016 El Niño-induced drought shocks in Zambia were associated with about 20 percent and 37 percent reductions in maize yields and per capita incomes respectively. Climate shocks such as droughts and floods at the Zambian national level reduce cotton production by an estimated 68 percent, and both maize and groundnuts by 33 percent (Braimoh, et al, 2018).…”
Section: (Iii)mentioning
confidence: 99%
See 3 more Smart Citations